Vir politične revolucije v osebni prelomni odločitvi - Kermauner, Taras (Slavistična revija, 1997)
The analysis deciphers the bases of Kocbek's decision to join the War of National Liberation and the communist revolution in his drama Mati in sin (Mother and son): what is presented in drama on an intimate, familial and personal level, is transposed to the social political and historical level. This creats the duality typical of all Kocbek's work: he supports the revolution on the one hand, while developing a free, autonomous, individual personality on the order. He synthesises and solves this " tattered" condition in two ways: with a regression to the Holy Comradeship and with the transition to Christian personalism. Hence, Kocbek plays an important role in creatin fascistic inseparability of idealized communism and consecrated Sloveneness, as well as propagating civility, libertarianism, and strong self-reflection.
Keywords: Kocbek, Edvard, 1904-1981; Kocbek, Edvard: Mati in sin; literarne študije; Slovene literature; slovenska dramatika; slovenska književnost